An analysis of the first steps of phenol adsorption-oxidation over coprecipitated Mn–Ce catalysts: a DRIFTS study - D'Alessandro, Oriana (2012)
A series of Mn–Ce(M) solids (M = K or Na), with molar ratios 100–0, 50–50 and 0–100 were prepared by co-precipitation of manganese and cerium nitrate from NaOH or KOH solutions at pH = 11. In addition, part of the solids precipitated with NaOH were dried and impregnated with a Cu²⁺ salt. The solids were characterized by XRD, Specific Surface Area, XPS and EDS. The characterization analyses show the formation of Mn mixed oxides with different oxidation states (Mn³⁺, Mn⁴⁺), for samples without Ce or Mn–Ce(M) 50–50. In the latter solid and in the one where there is no Mn, the formation of CeO₂ (fluorite type) was detected. The samples were tested in the phenol removal in water at 100 °C and at atmospheric pressure with the aim to analyze the adsorbed species in the first stage of the adsorption-oxidation mechanisms. The results indicate, on the one hand, that [MnOₓ] is the active species in the process and that the most active solids are those that present (i) a higher concentration of OI, (ii) a higher amount of Mn⁴⁺ ions. DRIFT spectroscopy showed a possible mechanism of phenol adsorption on two sites, in the first one by H interaction of OH (phenol) with an OH of the catalyst and in the second, by the formation of a phenolate species between an O (OH phenol) and Mnⁿ⁺.